1955
DOI: 10.1079/bjn19550005
|View full text |Cite
|
Sign up to set email alerts
|

The Nutritive Value of Colostrum for the Calf

Abstract: Examination of results obtained during the period 1949-54 has shown that newborn calves grow well when they are brought into our calfhouse after it has been left vacant for some time. When, however, they are brought in after the house has been occupied by a succession of experimental calves, their growth rate is less.It is well known that scouring can reduce the live-weight gain of calves, and we have now shown that the incidence of scouring and hence the live-weight gain of a particular calf is related to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1955
1955
1976
1976

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Earlier experiments on the effect of heat treatment of milk showed that milk diets, which had been heated sufficiently to denature a large proportion of the whey proteins, had a detrimental effect on the calf . When such diets were given after the colostrum-feeding period, they tended to predispose the calves to an Escherichia coli localized intestinal infection (Wood, 1955). Associated with the denaturation of the whey proteins is a reduction in ionizable calcium (Hostettler & Stein, 1958), the release of SH groups (Zweig & Block, I~C J ) , poor clotting ability by rennet (Shillam & Roy, 1963b), and reduced digestibility, but no effect on the biological value, of the protein (Shillam & Roy, 1963a powders were prepared by the same processes as powders A and B, used in the experiments of Shillam et al ( 1 9 6 2~~ b) and Shillam & Roy (1963a, b).…”
mentioning
confidence: 99%
“…Earlier experiments on the effect of heat treatment of milk showed that milk diets, which had been heated sufficiently to denature a large proportion of the whey proteins, had a detrimental effect on the calf . When such diets were given after the colostrum-feeding period, they tended to predispose the calves to an Escherichia coli localized intestinal infection (Wood, 1955). Associated with the denaturation of the whey proteins is a reduction in ionizable calcium (Hostettler & Stein, 1958), the release of SH groups (Zweig & Block, I~C J ) , poor clotting ability by rennet (Shillam & Roy, 1963b), and reduced digestibility, but no effect on the biological value, of the protein (Shillam & Roy, 1963a powders were prepared by the same processes as powders A and B, used in the experiments of Shillam et al ( 1 9 6 2~~ b) and Shillam & Roy (1963a, b).…”
mentioning
confidence: 99%
“…Some reduction in digestibility and utilization of fat during early life may have to be accepted for economic reasons, provided such diets do not predispose calves to scouring and a high death rate. However, in our experience, diets that are slightly inferior nutritionally to whole milk usually cause a very high incidence of mortality once other predisposing factors, such as a build-up of 'infection' (Roy, Palmer, Shillam, Ingram & Wood, 1955), begin to take effect. Thus, when a milk substitute contains a relatively large amount of fat, it would seem advisable to use an homogenized product during at least the first 2 weeks of life rather than one in which the fat had been emulsified with lecithin.…”
mentioning
confidence: 77%
“…The affecting variables were : x5 = 'occupation time' (log days). 'Occupation time' is defined by Roy, Palmer, Shillam, Ingram & Wood (1955) as the number of days that the calfhouse had been occupied after a period of vacancy. That part of the residual error due to differences between treatments within each experiment was removed before analysis, as was that part of the error due to differences between blocks in two of the experiments.…”
Section: Part I Calculation Of the Requirement Of The Calf In Terms mentioning
confidence: 99%